Islam Mazhab Cinta ala Kiai Amin Maulana Budi Harjono Al-Jawi, 1990-2021: Pemikiran Tasawuf Seorang Kiai Sufi - Izul Adib; Rabith Jihan Amaruli (Jurnal Sejarah Citra Lekha, 2022)
This article discusses the Kiai Amin Maulana Budi Harjono Al-Jawi (hereinafter referred to as Kiai Budi)’s thoughts about sufism, from 1990 to 2021. Kiai Budi was the caretaker of Al-Ishlah Islamic Boarding School, Semarang who was known as a Sufi kiai. Kiai Budi’s important contribution is his ability to translate Sufism ideas that are difficult to be easily understood by common people. Through four stages in the historical method, this research uncovers the factors behind the birth of Kiai Budi’s thought. Interpretation of the personal side of a Kiai Budi and his social actions through a social hermeneutic approach, has revealed the style, substance, and implementation of Kiai Budi’s thoughts which are passionate about Sufism themes. Sufism, which he calls Islam Mazhab Cinta/Islam the School of Love, can be categorized in several aspects, namely monotheism, social relations, Islam and nationality, as well as art and culture. In practice, Kiai Budi’s thoughts have been implemented through the formation of the Sufi Dance group and the Sedulur Caping Gunung Movement.